Interaction of Trypanosoma cruzi with Host Cells - Wanderley De Souza (Frontiers Research Topics, 2014)
Trypanosoma cruzi is a pathogenic protozoan of the Trypanosomatidade Family, which is the etiological agent of Chagas' disease. Chagas' disease stands out for being endemic among countries in Latin America, affecting about 15 million people. Recently, Chagas has become remarkable in European countries as well due to cases of transmission via infected blood transfusion. An important factor that has exacerbated the epidemiological picture in Brazil, Colombia and Venezuela is infection after the oral intake of contaminated foods such as sugar cane, açai and bacaba juices. Trypanosoma cruzi is an intracellular protozoan that exhibits a complex life cycle, involving multiple developmental stages found in both vertebrate and invertebrate hosts. In vertebrate hosts, the trypomastigote form invades a large variety of nucleated cells using multiple mechanisms. The invasion process involves several steps: (a) attraction of the protozoan to interact with the host cell surface; (b) parasite-host cell recognition; (c) adhesion of the parasite to the host cell surface; (d) cell signalling events that culminate in the internalization of the parasite through endocytic processes; (e) biogenesis of a large vacuole where the parasite is initially located, and is also known as parasitophorous vacuole (PV); (f) participation of endocytic pathway components in the internalization process; (g) participation of cytoskeleton components in the internalization process; (h) transformation of the trypomastigote into the amastigote form within the PV; (i) lysis of the membrane of the PV; (j) multiplication of amastigotes within the host cell in direct contact with cell structures and organelles; (k) transformation of amastigotes into trypomastigotes, and (l) rupture of the host cell releasing trypomastigotes into the extracellular space. The kinetics of the interaction process and even the fate of the parasite within the cell vary according to the nature of the host cell and its state of immunological activation.